(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pulmonary embolism (PE) is a potentially life-threatening cardiovascular emergency that requires prompt diagnosis and treatment. Although CT Pulmonary Angiography (CTPA) remains the gold standard for diagnosis, it may not always be readily available and exposes patients to radiation and contrast-related risks. D-dimer, a fibrin degradation product, has emerged as a useful biomarker for the evaluation of suspected PE due to its high sensitivity. Aim: To evaluate the diagnostic utility of plasma D-dimer levels in detecting pulmonary embolism among patients with clinical suspicion of PE. Materials and Methods: This prospective observational study was conducted among 25 adult patients presenting with clinical features suggestive of pulmonary embolism. Plasma D-dimer levels were measured using an immunoturbidimetric assay. All participants subsequently underwent CT Pulmonary Angiography, which served as the reference standard for diagnosis. Demographic characteristics, clinical presentations, D-dimer values, and CTPA findings were recorded and analyzed. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of D-dimer were calculated. Results: The mean age of the study population was 49.8 ± 13.4 years, with males accounting for 56.0% of participants. Dyspnea was the most common presenting symptom (88.0%). Elevated D-dimer levels (>500 ng/mL) were observed in 68.0% of patients. Pulmonary embolism was confirmed by CTPA in 10 (40.0%) patients. A significant association was observed between positive D-dimer results and confirmed PE (p = 0.019). D-dimer demonstrated a sensitivity of 90.0%, specificity of 46.7%, PPV of 52.9%, NPV of 87.5%, and an overall diagnostic accuracy of 64.0%. Conclusion: D-dimer is a highly sensitive screening tool for pulmonary embolism and possesses a high negative predictive value, making it useful for excluding PE in clinically suspected patients. However, its relatively low specificity limits its utility as a standalone diagnostic test. D-dimer should be interpreted in conjunction with clinical assessment and imaging findings.